Response Prediction of Static Modal Testing on Milling Machine Tool - Norlida, Jamil; Ahmad Razlan, Yusoff; Muhammad Hatifi, Mansor (Trans Tech Publications Ltd., 2014)
Milling is one of the most common manufacturing processes for automotive component, but its productivity is limited by chatter. This form of chatter is undesirable because it results in premature tool wear, poor surface finish on the machined component and the possibility of serious damage to the machine itself. Modal testing is a form of vibration testing which is able to determine the Frequency Response Function (FRF) of the mechanical test structures. In this paper, the main focus is to obtain natural frequency values for machine tool components in order to establish better conditions in the cutting process on the machine tool. For this purpose, a 3D model of the machine tool’s part is made using design software and exported to analysis software. Later on, the Finite Element Method (FEM) modal analysis was used to obtain the natural frequencies. The model is evaluated and corrected through an experimental modal test. In the experiment, the machine tool vibration is excited by impact hammer and the response of excited vibration is recorded. In the end, the result of both FEM and experimental shows a good consistency in comparison.